Analysis of Generation, of Household Waste and Its Potential Utilization in Darul Imarah subdistrict - Aceh Besar District - Sofia, Sofia; Kartini, Kartini; Zubir, Zubir (Open Access Macedonian Journal of Medical Sciences, 2021)
Abstract BACKGROUND: Darul Imarah District is one of the largest sub-districts in Aceh Besar, which is very dense and faces a waste problem. The increase in population in the Darul Imarah sub-district has resulted in waste generation. AIM: analyzing the generation, composition of household waste and its potential use in Darul Imarah subdistrict, Aceh Besar District, Aceh Province METHODS: This study used a cross-sectional study design by conducting an initial survey on the generationvolume and composition of waste in each house selected as a sample and continued with an experimental study. The research object is solid wastegarbage generated from daily activities in the selected sample group households in the Darul Imarah sub-district in the form of primary data from sampling, with a random sampling technique. The number of samples of 100 houses with the respondent's target is housewives. Data analysis was carried out using the T-Test difference test to compare the value before being given knowledge about household waste management after being given knowledge. RESULTS: The study results show differences in the generation and composition of waste before and after being given knowledge about household waste management in Darul Imarah District, Kab. Aceh Besar with a significant (sig.) Of 0.000 (0.05). The total waste produced before being given knowledge about waste management was 164.6 kg. The composition of the waste consists of plastic waste (22.9 kg), wet waste (62.5 kg), dry waste (37.4 kg), and glass waste (41.8 kg). After being given knowledge about waste management, there was a reduction in the total waste produced, namely 131.8 kg. A significant reduction in the amount of waste in the volume of plastic waste (7.8 kg), wet waste (48.0 kg), dry waste (37.3 kg), and glass waste (38.8 kg). There is a difference in the volume of plastic waste in plastic waste after being given knowledge about household waste management, with the difference between the average before and after is 0.1530 and the difference is between 0.1045 - 0.2015 (95% Ci). In wet waste, there is a difference in the volume of wet waste after being given knowledge about household waste management with the difference between the before and after averages of 0.1450 and the difference between the differences is between 0.0784 - 0.2116 (95% Ci). In dry waste, there is no difference in the volume of dry waste after being given knowledge about household waste management with an average difference before and after of 0.0020, and the difference is between -, 0008 - 0.0048 (95% Ci). There is a difference in the volume of glass waste in glass waste after being given knowledge about household waste management with the difference between the before and after an average of 0.0310 and the difference between the differences between 0.0170 - 0.0450 (95% Ci). CONCLUSION: There are differences in the generation and composition of waste before and after being given knowledge about household waste management in Darul Imarah District, Kab. Aceh Besar with a significant (sig.) of 0.000 (0.05).